EUS‐guided 22‐gauge fine‐needle aspiration versus core biopsy needle in the evaluation of solid pancreatic neoplasms. Issue 9 (18th February 2014) - Strand, Daniel S.; Jeffus, Susanne K.; Sauer, Bryan G.; Wang, Andrew Y.; Stelow, Edward B.; Shami, Vanessa M.
<x xml:space="preserve">Abstract</x> Endoscopic ultrasound‐guided fine‐needle aspiration (EUS‐FNA) is widely used for diagnosis of pancreatic lesions. The Echotip Procore Needle (Wilson‐Cook Medical) is a new 22G fine biopsy needle (FNB) for obtaining core biopsy material at time of EUS. This study aimed to compare the technical and diagnostic performance of conventional FNA and FNB. Thirty‐two patients met the design criteria for this prospective paired cohort study. All lesions sampled were solid (non‐cystic) pancreatic masses by EUS appearance. Patients were randomized to receive FNA or FNB by first attempt. A cytopathologist performed on‐site evaluations. Samples were assessed for accuracy of diagnosis, cellularity, contamination, and sufficiency for ancillary studies. Technical and diagnostic performances were compared. Compared to FNA, there was a statistically significant decreased ability of FNB to achieve a diagnosis (FNA 93.8%, FNB 28.1%, P < 0.001). FNB was diagnostically superior to FNA in 1 of 32 cases. Technical failures were observed in five cases due to resistance to advancement of the FNB needle. Regarding operator perceived ease‐of‐use, FNA outperformed FNB (P < 0.001). Eight cases had insufficient FNB material to survive tissue processing. There was no significant difference in mean specimen cellularity between devices. FNA samples showed an increased amount of contaminant (P = 0.036) but were more sufficient for ancillary studies (P = 0.502). Although deemed comparable to FNA when providing material for cytology, the pledged advantage of FNB acting like a core biopsy needle was not apparent in our series. Additional studies are needed before routine adoption of 22G FNB can be recommended. Diagn. Cytopathol. 2014;42:751–758. © 2014 Wiley Periodicals, Inc.